Aplikasi Pengelolaan Data Surat Pertanggungjawaban (SPJ) Jurusan Manajemen Informatika Berbasis Website Pada Politeknik Negeri Sambas - Renol Burjulius; Mareta Mareta; Sonty Lena (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2023)
The management of accountability letters in the Informatics Management department, especially in data storage, is still in the form of sheets of paper and there is no data storage in the form of applications. This study designed and created a data management application for a letter of accountability (SPJ) on the Information Management majors website based. In developing this system using the Prototyping method, PHP as a programming language and using the MySQL database. With this accountability letter data management application (SPJ), it is hoped that it will make it easier for staff at the Informatics Management study program to manage the storage of accountability letters, because they are not only stored in the form of sheets of paper but are also stored in the application database. As well as to make it easier to search for the desired accountability letter.